The Characterization Of Hydroxyapatite, Eppigalocathecine-3-Gallate, Hydroxypropyl Methylcellulose As Bioactive Material For Pulp Capping - Elline, Elline; Suwartini, Tien; Komariah, Komariah; Lambertus, Reynaldo (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: According to a previous study, hydroxyapatite (HA) has the potential to be used in dentistry, but it still needs further research, especially as a biomaterial for pulp capping. The pulp capping treatment can maintain pulp vitality and induce dentin reparative formation. Calcium hydroxide is the gold standard of pulp capping material, but it can cause tunnel defects. Several studies made a crosslink with epigallocatechin-3-gallate (EGCG) and hydroxypropyl methylcellulose (HPMC) to improve the effect of hydroxyapatite as a biomaterial. The HA-EGCG-HPMC combination is expected to have the potential as a bioactive material. In this study, HA-EGCG-HPMC was characterized physicochemically by several criteria, such as the gelation time, pH, and antibacterial effect against Aggregatibacter actinomycetemcomitans. This study aims to determine the physicochemical characteristics of the HA-EGCG-HPMC material as a pulp capping materialMethod: This research is an in vitro laboratory experimental study design. Hydroxyapatite powder was dissolved with distilled water at concentrations of 4%, 2%, and 1%, with 10µmol/mL EGCG and hydroxypropyl methylcellulose as the carrier agent. Characterization of the samples measured are gelation time, pH, and antibacterial effect by microdilution method. Result: The HA-EGCG-HPMC combination has an ideal gelation time of about 23-31 minutes, and its pH is within the range of 7.28 - 7.33. However, the HA-EGCG-HPMC does not yet have an antibacterial effect against Aggregatibacter actinomycetemcomitans.Conclusion: The hydroxyapatite, EGCG, and hydroxypropyl methylcellulose can be used as a bioactive material, such as pulp capping material seen from physicochemical characterization that can be developed further.